Using a wearable camera to increase the accuracy of dietary analysis - O'Loughlin, G; Cullen, S; McGoldrick, A; O'Connor, S; Blain, R; O'Malley, S; Warrington, G (Elsevier, 2013)
Background: Food diaries are commonly used to assess individual dietary intake in both the general and sporting populations. Despite the widespread use of such diaries, evidence suggests that individuals' self-reported energy intake frequently and substantially underestimate true energy intake. Purpose: To examine the use of the Microsoft SenseCam wearable camera to help more accurately report dietary intake within various sporting populations. Methods: In 2011, a total of 47 participants were recruited to take part in this study (17 trainee jockeys, 15 elite Gaelic footballers, and 15 healthy physically active university students). Participants wore a SenseCam for 1 day (from morning until night) while simultaneously keeping a 1-day food diary. Comparisons were made between the energy intake reported in the food diary in conjunction with information gathered from the SenseCam. Data analysis was conducted in 2012. Results: Mean total calorie intake using diary alone and diary and SenseCam were 2349±827.9 kcals vs 2631±893.4 kcal for the trainee jockeys; 2600±521.9 kcal vs 3191±770.2 kcal for the Gaelic footballers, and 2237±318.5 kcal vs 2487±404.6 kcal for the university students. This represented a difference of 10.7% (p≤0.001); 17.7% (p≤0.001); and 10.1% (p≤0.001) among measurement methods for trainee jockeys, Gaelic footballers, and university students, respectively. Conclusions: Results from this first-generation study suggest that a more accurate estimate of total energy intake is provided when combining the use of a conventional food diary and a SenseCam. Additional information on portion size, forgotten foods, leftovers, and brand names can be obtained by using this novel sensing technology in conjunction with the diary, with improved dietary assessment a potential outcome.